Pengawasan dan Pengamatan Pelaksanaan Putusan Pengadilan: Studi Kasus Tindak Pidana Anak - Andi Purnawati; Ilham Ilham (Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This study aims to determine the role of the Supervisor and Observer Judge and to analyze the factors influencing the implementation of Court Decisions against child crimes in the Class IIA Penitentiary of Maros. This research uses empirical legal research methods. The primary data collection was carried out using a questionnaire, while the secondary data was collected using literature study techniques. The data obtained in this research is quantified using a quantitative descriptive analysis model, then described using a frequency distribution table for answer research purposes. The results show that the role of the Supervisor and Observer Judge is not limited to supervising and observing child convicts during their punishment period at the Penitentiary but also supervising and observing child convicts after they leave the Penitentiary or have finished their punishment period and return to society. Furthermore, three dominant factors influence the implementation of Court Decisions against child crimes in the Class IIA Penitentiary of Maros: the law enforcer factor, the facilities factor, and the community factor. Awareness of child convicts as a community factor has positively influenced the implementation of the Maros District Court Decision. Therefore, it is recommended for the Supervisor and Observer Judge to maximize their role. In this case, the role of the judge must supervise and observe the activities of child convicts and the role of Correctional Officers in implementing Court Decisions in the Class IIA Penitentiary of Maros. In addition, it is suggested to the Minister of Law and Human Rights make regulations regarding the proportion of the Supervisor and Observer Judge to the number of convicts in the Penitentiary so that the implementation of Court Decisions can run optimally in the future.